The law of tax-exempt healthcare organizations - Hyatt, Thomas K. (J. Wiley & Sons, 2008)
This book provides a comprehensive, one-volume source of detailed information on federal, state, and local laws covering tax-exempt healthcare organizations. It tackles complex legal issues in a practical, down-to-earth manner by providing plain-English e.